DEVELOPMENT OF ANDROID-BASED INTERACTIVE LEARNING MEDIA IN BASIC GRAPHIC DESIGN SUBJECTS AT VOCATIONAL SCHOOLS - Aisyah Putri; Dasminar Dasminar; Delfa Delfa; Levi Levi; Mawar Mawar; Yadika Yadika (INFOKUM, 2023)
The problem in this study is that students do not understand the material as a result of which many students score low, lack of interest in learning and student motivation in the teaching and learning process, there is no android-based interactive media. The purpose of this study was to design interactive android-based learning media in the class X Basic Graphic Design subject at SMKN 1 X Koto Above using the smart app creator application, as well as knowing the quality of the media in designing Android-based interactive learning media in the Basic Graphic Design class. X at SMKN 1 X Koto Above. The method used in this study is MDLC (Multimedia Development Life Cycle) which consists of 6 stages namely Concept, Design, Material Collecting, Assembly, Testing, Distribution. By using alpha and beta testing. Alpha testing is carried out using the Black Box method, while beta testing includes material validity, media validity and user feasibility testing. The results of the Black Box test properly, beta test results on material validation 0.95% with the valid category, 0.94% media test results with the valid category, user feasibility test 88.8%, with very good category.